Mycological assessment of the waters of the Araz River in the territory of the Republic of Azerbaijan - P.Z, Muradov; K.F, Bakhshaliyeva; V.K., Isayeva; S.M, Muradova; S.F., Azadaliyeva (Edelweiss Applied Science and Technology, 2026)
The purpose of the presented work was to analyze the fungal biota of the Araz River, which is the largest tributary of the Kura River and is considered a transboundary river, from the point where it enters the territory of the Republic of Azerbaijan to the point where it joins the Kura River. It has become clear that fungi are found in river waters in any season, and their number varies between 500 and 1900 CFU/ml. It was determined that 41 fungal species participated in the formation of the mentioned number, which are characterized by wide diversity in terms of their taxonomic structure and forms of manifestation of ecotrophic specialization (conditionally pathogenicity, toxigenicity, phytopathogenicity, etc.). Despite the fact that fungi participate in a wide range of functions in any ecosystem, there are still no normative indicators regulating the use of fungi in the biomonitoring of aquatic ecosystems. The results of studies conducted in a specific area allow us to note the importance of preparing such a document, especially in a situation where biological pollution of waters is inevitable.